O amor e a guerra em Aristófanes a partir de uma leitura da Peça Rãs - Amaro, Márcio Henrique Vieira (2015)
Based on a reading of the play The Frogs, 405 b.C., by Aristophanes, it’s inferred a strong use of mythological material used by the comediographist in the construction of the text. Therefore, a reading of that comedy under the modern scientific approaches to the myth allows the determination of a mythical nucleus able to offer an important key to reading the work of Aristophanes as well as the dramatic production of the late classical Greek period. In the agon between Aeschylus and Euripedes, the tragic themselves are the ones who, insulting each other, reveal the source of their production to be, respectively, the influence from the myths of Ares and Aphrodite. Both the tragedians being members of the triad elected by the Athenians as the best representatives of the tragic genre, and, the poetry being one of the constituent sources of the Greek citizen’s education, this research will verify to what extent the myths of Ares and Aphrodite are present in the work of the two tragedians, and how both use it as a contribution to the foundation for the shaping of the Greek man’s spirit. From a dialectic between love and war, the second part of the research will verify the occurrences of these traditions in the work of the comediographist Aristophanes, analyzing the play The Frogs. The author, when choosing the kingdom of the dead as a discussion space between these two mythological traditions, establishes a paradigmatic court, able to appreciate and value the diferent elements and types of tragic speech, treating them, however, under the comical perspective. It is necessary to determine to what extent the comic speech from the parallel between the underground structures and the contingency of Athenian life were being used as an attempt to interpret the myth. Finally, will verify with the presentation of the play Frogs, the comedy would be, in 405 b.C., seeking to appropriate the mythological speech, modifying it and shaping it according to the new requirements of the polis, as the tragic did before, and what are the implications of this new discourse on the elements related to theater: text, performance and audience.